FINANCIAL RATIO ANALYSIS TO ASSESS COMPANY PERFORMANCE AT PT GLOBAL TELESHOP TBK ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2017–2021 - Jarot Wuryanto; Lakonardi Nurraditya; Mujito . (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to assess the financial performance of PT Global Teleshop Tbk for the period 2017–2021 based on liquidity, profitability, solvency, and activity ratio analysis. The research uses a descriptive qualitative method. The population consists of the financial statements of PT Global Teleshop Tbk, with the sample being the company's financial reports from the last five years (2017–2021). The data analysis uses financial ratios. The results show that: (1) The liquidity ratio analysis indicates good financial performance, as shown by the increasing Current Ratio (CR) and Quick Ratio (QR), demonstrating the company's improving ability to meet short-term liabilities with liquid current assets, although the QR still falls into the less optimal category; (2) The profitability ratio analysis indicates poor performance, with low Net Profit Margin (NPM) and Return on Equity (ROE), showing the company's limited ability to generate profits from shareholders' funds; (3) The solvency ratio analysis shows weak financial performance, with Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) indicating the company’s inability to cover total liabilities with its assets; (4) The activity ratio analysis, based on Total Asset Turnover (TATO) and Working Capital Turnover (WCT), also suggests poor performance due to declining asset turnover and ineffective management of working capital.